2012
DOI: 10.1161/atvbaha.111.238964
|View full text |Cite
|
Sign up to set email alerts
|

ApoE Suppresses Atherosclerosis by Reducing Lipid Accumulation in Circulating Monocytes and the Expression of Inflammatory Molecules on Monocytes and Vascular Endothelium

Abstract: Objective We investigated atheroprotective properties of apoE beyond its ability to lower plasma cholesterol. We hypothesized that apoE reduces atherosclerosis by decreasing lipid accumulation in circulating monocytes and the inflammatory state of monocytes and the vascular endothelium. Methods and Results We developed mice with spontaneous hyperlipidemia with and without plasma apoE: Hypomorphic apoE mice deficient in low-density lipoprotein receptor (Apoeh/hLdlr–/–) were compared to Apoe–/–Ldlr–/– mice. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 40 publications
3
55
1
1
Order By: Relevance
“…Further, aortic lesions were signifi cantly reduced in these mice 3 months after initiating feeding with a Western diet ( 97 ). Protective effects of apoE have been observed in the context of coagulation, macrophage function, oxidative processes, central nervous system physiology, infl ammation, and cell signaling ( 98,99 ). Data suggest that anti-infl ammatory reduce infl ammatory injury in murine models of multiple sclerosis and traumatic brain injury, respectively, and are thought to mediate their effects via binding to LRP (128)(129)(130).…”
Section: Anti-atherogenic Mechanisms Of Apoe Actionmentioning
confidence: 98%
See 2 more Smart Citations
“…Further, aortic lesions were signifi cantly reduced in these mice 3 months after initiating feeding with a Western diet ( 97 ). Protective effects of apoE have been observed in the context of coagulation, macrophage function, oxidative processes, central nervous system physiology, infl ammation, and cell signaling ( 98,99 ). Data suggest that anti-infl ammatory reduce infl ammatory injury in murine models of multiple sclerosis and traumatic brain injury, respectively, and are thought to mediate their effects via binding to LRP (128)(129)(130).…”
Section: Anti-atherogenic Mechanisms Of Apoe Actionmentioning
confidence: 98%
“…The synthesis and application of HDL-like nanolipid particles is a recent development in the fi eld of HDL therapy. Earlier, it was shown that, among the 22mer helices of apoA-I, only the N-and C-terminal helices were able to associate with phospholipids while the other regions (either effects of the apolipoprotein are independent of its cholesterol-lowering property (99)(100)(101)(102). Polymorphisms in the apoE gene are associated with enhancement of the infl ammatory response and an increase in mortality in animal models and patients with sepsis ( 103,104 ).…”
Section: Clinical Evaluation Of the Apoa-i Mimetic Peptide 4fmentioning
confidence: 99%
See 1 more Smart Citation
“…The inducible repair of the hypomorphic phenotype can promote regression and stabilization of atherosclerosis (59,60). The hypoE mice and Apoe / mice were crossed with Ldlr / mice, with the genetic background of the mice being 85% C57BL/6 and 15% 129SvJ (61). Less atherosclerosis was seen in the hypomorphic animals on chow diet.…”
Section: Non-hepatic Apoe and Atherosclerosismentioning
confidence: 99%
“…The antiproliferative effect is likely due to endogenous apoE bound to the surface of HPSCs interacting with ABCA1 and ABCG1 to promote lipid efflux, resulting in decreased signaling in response to growth factors (80). Monocytosis, particularly of the Ly6C hi subclass, is a risk factor for atherosclerosis (84 (61). This could be a response to an improved cholesterol efflux from the HPSCs in the hypomorphic mice in whom there was a redistribution of some of the plasma apoA-I from VLDL to HDL, making for a more efficient cholesterol efflux acceptor.…”
Section: Coronary Atherosclerosis and Myocardial Infarction Inmentioning
confidence: 99%